2020
DOI: 10.1051/e3sconf/202021009005
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of transport routes based on environmental indicators

Abstract: Air pollution monitoring in Rostov-on-Don and Rostov region is considered. The excess of the concentration of suspended solids over the national average is shown, especially near motorways and the busiest intersections. On the example of one intersection, field observations were carried out, and based on the developed computer programs, calculation of the main transport characteristics, the vehicle queue length at different phases of traffic light switching was carried out. The necessity of installing a "smart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Also, to automate the operation of a modern agricultural combine, it is required: a control unit, various sensors to control the load on the working organ, the weight of grain on the conveyor belt, etc. In an agricultural machine with the proposed intelligent mechanism, adaptation to changing working conditions occurs due to the mechanical operation of two differential drives, as a result of which there is no need for the above mechanisms [7][8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Also, to automate the operation of a modern agricultural combine, it is required: a control unit, various sensors to control the load on the working organ, the weight of grain on the conveyor belt, etc. In an agricultural machine with the proposed intelligent mechanism, adaptation to changing working conditions occurs due to the mechanical operation of two differential drives, as a result of which there is no need for the above mechanisms [7][8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…One practical way to apply these algorithms to the real world is to use smart traffic lights. A study showed smart traffic lights using cue lengths and other traffic data to calculate optimal turning times would reduce the idling time of vehicles in that intersection [27]. The researchers compared a traffic light with a fixed signal to a traffic light with an adaptive smart algorithm.…”
Section: Prediction and Control Of Traffic Flowmentioning
confidence: 99%
“…They are associated with determining the most optimal strategies for development based on methods for modeling the relationships between traffic flows [3] and objects of a multimodal transport network [4], conducting expert assessments of individual projects and strategies for the development of transport infrastructure based on the achievements of logistics [5,6]. Moreover, the main goal of such strategies and projects is to increase the capacity of corridor lines for the transport of goods after their modernization [7].…”
Section: Introductionmentioning
confidence: 99%